Sport Tourism Potential of Lahe Island, Marisa District, Pohuwato Regency, Gorontalo Province - Wal Asri T Muko; Heny Setyawati; Setya Rahayu (Journal of Physical Education and Sports, 2023)
This research aims to analyze the potential strengths, weaknesses, opportunities, and threats in the development of sports tourism in Lahe Island, Marisa Sub-district, Pohuwato Regency, Gorontalo Province. Qualitative method with explorative approach was used in this research. Sources of data Person Head of Tourism of Pohuwato Regency, Tourists, Communities, and Businessmen, Lahe Island Place, Paper Supporting documents. Data collected through observation, interviews and documentation, Data validity techniques using source triangulation and method triangulation, analyzed using SWOT. The results showed that the strength of Lahe Island lies in its beautiful natural resources such as white sandy beaches and diverse marine life as well as interesting sports activities such as camping/survival and diving. Weaknesses are inadequate facilities/infrastructure and lack of information about Lahe Island. Great opportunities for Lahe Island in increasing regional tourism through annual events from the Government as well as water sports activities by the POSSI (Indonesian Diving Sports Association) and Free Dive organizations. Threats faced are weather changes that can affect tourism activities and natural damage that threatens the sustainability of Lahe Island's natural resources. Conclusion Lahe Island has great potential as a sports tourism destination with its natural beauty to optimize the potential requires efforts to develop facilities / infrastructure, more intensive promotion, and active involvement of relevant stakeholders to maintain the sustainability of tourism on Lahe Island.